INCREASING COMMUNITY KNOWLEDGE ABOUT HYPERTENSION WITH A DIRECT EDUCATION PROGRAM AS AN EFFORT TO IMPROVE COMMUNITY HEALTH STATUS - Buyung Reza Muhammad Buyung Reza Muhammad; Rudy Alfiyansyah Rudy Alfiyansyah; Andhika Lungguh Perceka Andhika Lungguh Perceka (LP4M STIKes Karsa Husada Garut, 2024)
A community is a group of people who share common values and concerns as a special group with clear geographic boundaries, with institutionalized norms and values. Hypertension or High Blood Pressure is a condition where systolic blood pressure ≥ 140 mmHg and or diastolic blood pressure ≥ 90 mmHg. Hypertension is often called “the silent killer” because it is often without complaints, so the patient does not know that he has hypertension, but later finds himself already having complications or complications from hypertension. The purpose of this community service activity is to increase knowledge about hypertension through good understanding which is carried out door to door to each resident's house. The method used is through door to door visits to each resident's house and health counseling through lectures and questions and answers. The results of the health counseling have been known that the participants are very active in participating in this activity. Evaluation of participants' knowledge was done by comparing their answers to several questions during hypertension screening and after counseling. After the counseling, the participants were able to answer an average of 8 questions correctly, while before the counseling, the participants answered an average of only 3 correct answers.